Analisis sajian buku teks pelajaran untuk memfasilitasi terlaksanaannya ketrampilan proses sains pada pembelajaran fisika kelas XII semester 2 - Bella Sukma Putri; Desnita Desnita; Asrizal Asrizal; Yenni Darvina (Universitas Negeri Padang, 2020)
Science Process Skills (SPS) are skills used in scientific inquiry that can facilitate students discovering facts, concepts, and can apply theories in everyday life. One of the supporting science process skills is the textbook. Textbooks are the main source of learning in the learning process. The use of textbooks in West Sumatra varies greatly. This study aims to determine the level of SPS offers in textbooks used in secondary schools in West Sumatra. This research is a descriptive study using a qualitative approach with a population of all physics textbooks for Class XII semester 2 published in Indonesia and used in secondary schools in West Sumatra. The sample of this study were four Physics textbooks that were most widely used in secondary schools in West Sumatra and three of them were recommended by the Ministry of Education and Culture. The instrument used was validated by 3 experts. the first expert got a value of 0.98% categorized as very valid, the second expert obtained a value of 0.96 categorized very valid and the third expert got a value of 0.85 categorized as very valid. The validated instrument has 10 components and is defined on each indicator to be 37 instrument points. Data collection techniques used were interviews and documentation. The results were obtained that physics textbooks written by Muhammad Farchani Rosyid, and published by the Triumvirate in 2016, had the highest SPS bid level, whereas physics textbooks written by Marthen Kanginan and published by Erlangga in 2017 had the lowest SPS service level.